Perfil dos usuários da clínica odontológica da Secretaria de Assuntos Comunitários da Universidade Federal do Espírito Santo - Rasseli, Rozane Cristina Schwab Alves (2013)
Oral health is an essential component of general health that is why it is relevant and necessary that oral health services know the profile of their consumers with the intent to improve the quality of services. With that in mind, the objective of this study was to identify the profile of consumers seen at the Department of Community Issues (SAC), currently known as the Health Attention Department (DAS) of the Federal University of Espírito Santo (Ufes). A sectional descriptive study was conducted, analyzing the charts of 415 patients who received dental treatment at SAC/DAS/Ufes between July 2010 and July 2012. An instrument was elaborated with the objective of registering and organizing the information gathered in the charts, which included: demographic data, health history, oral health habits and its conditions and reasons for treatment search. The majority of consumers were over 40 years old, and female was the most prevalent gender 59.8%. It was verified that 40% of consumers were federal employees and 34.7% were college students. As for the main reason for treatment search, 51.6% of the clinic consumers identified it to be for maintenance, 22.9% for prevention and 14% due to cavity disease. In relation to dental hygiene habits, every consumer use a tooth brush (100%), 20% do not use dental floss, and 34.2% of those who use dental floss, do so once a day. Only 28.9% of consumers have been without an dental consult for one year or less. In conclusion, the consumer s profile of SAC/DAS/Ufes reflects the model adopted by the health institution; however, changes in the dental model offered at SAC/DAS/Ufes are necessary to transition from the surgical restoration model to an oral health promotion model.